Resistance training, antioxidant status, and antioxidant supplementation - Ismaeel, A.; Holmes, M.; Papoutsi, E.; Panton, L.; Koutakis, P. (International Journal of Sport Nutrition and Exercise Metabolism, 2019)
Resistance training is known to promote the generation of reactive oxygen species. Although this can likely upregulate the natural, endogenous antioxidant defense systems, high amounts of reactive oxygen species can cause skeletal muscle damage, fatigue, and impair recovery. To prevent these, antioxidant supplements are commonly consumed along with exercise. Recently, it has been shown that these reactive oxygen species are important for the cellular adaptation process, acting as redox signaling molecules. However, most of the research regarding antioxidant status and antioxidant supplementation with exercise has focused on endurance training. In this review, the authors discuss the evidence for resistance training modulating the antioxidant status. They also highlight the effects of combining antioxidant supplementation with resistance training on training-induced skeletal muscle adaptations.